Beneficial Effects of Mindfulness-based Cognitive Therapy on Resilience and Psychological Distress in Patients Recovered From COVID-19 - Zahra Malekpour Golsefidi; Farnaz Keshavarzi Arshadi; Suzan Emamipour (Gonabad University of Medical Sciences, 2022)
Background: The medium and long-term problems of COVID-19 survivors after hospital discharge are currently unknown, but new evidence is emerging. This study was conducted with the aim of the effectiveness of mindfulness-based cognitive therapy (MBCT) on resilience and psychological distress of recovered patients from COVID-19 in Tehran City, Iran, in 2021. Methods: The study was a quasi-experimental type of pre-test-post-test design with a control group with a 2-month follow-up. The statistical population included all patients 25-55 years in Tehran City in 2021 with 4 to 8 weeks of discharge. The sample included 30 people who recovered from COVID-19 who had symptoms of depression, anxiety, and stress (based on [depression, anxiety and stress scale] DASS-21 scores) and was selected by purposive sampling and based on the inclusion criteria, and then matching assigned to an experimental (MBCT) and a control group (n=15each). The experimental group received 8 sessions of 60 minutes of mindfulness-based cognitive therapy (individual and online) but the control group received no intervention. The research tools were the DASS-21 and Connor-Davidson resilience scale (CD-RISC). Data were analyzed using a mixed analysis test and Ben Foroni post hoc test using SPSS version 23 software. Results: The results showed that MBCT in the post-test positively affected the resilience (F=30.31, P=0.001) and negatively affected the psychological distress (F=120.70, P=0.001) of those who Recovered from COVID-19. This therapeutic effect continued until the follow-up phase. According to the results, MBCT is effective in increasing resilience and reducing psychological distress and a significant difference is observed between the experimental and control groups (P=0.01). Conclusion: Based on the findings, MBCT is effective in increasing resilience and reducing psychological distress after illness and the use of this model can be useful in the psychological rehabilitation of those who have recovered from COVID-19.